Correlation of the HER-2 protein expression and other clinicopathological features of ductal infiltrative breast cancer - Svjetlana Radović; Mirsad Babić; Mirsad Dorić; Edina Balta; Erol Kapetanović; Senad Šečić (Biomolecules & Biomedicine, 2005)
The aim of the study was to investigate the relationship between the expression of the HER-2 membrane protein and other clinical-pathological parameters such as: histological size of the tumor, degree of the tumor's differentiation, presence of vascular invasion and presence of metastases in regional lymph nodes, in cases of ductal infiltrative breast cancer. We have investigated 56 cases of ductalinfiltrative breast cancer. In all patients a mastectomy with a dissection of axillary lymph nodes has been performed. All tissue samples, taken by biopsy, were embedded in the paraffin, stained by hematoxylin-eosin technique and screened, and evaluation was performed by using a semiquantitative method of the immunohistochemical expression of the HER-2 protein. A decrease of the protein HER-2 expression was noticed in cases of an increase of the tumor's diameter above 50 mm. Increased expression of the HER-2 protein was noticed in cases of moderate (grade II) and poor (grade III) differentiation of carcinoma, as well as in cases where there was no metastases in the regional lymph nodes. No relationship has been observed between the expression of HER-2 and occurrence of vascular invasion. In cases of ductalinfiltrative breast cancer the expression of HER-2 protein is in correlation with the size and degree of tumor's differentiation, as well as with the presence of metastases in regional lymph nodes.